COMMON FIXED POINT THEOREM FOR WEAKLY COMPATIBLE MAPPINGS IN HILBERT SPACE - Modi, Geeta; Gupta, R.N (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper we prove a common fixed point theorem for weakly compatible mappings satisfies certain contractive condition in non- empty closed subset of a separable Hilbert Space. Our results generalize and extend the result Chauhan [7].